Alternatives of Non-hormonal therapy in the climacteric: A narrative review and promising new treatment - Silva, Mariana Leite Rosa Pinheiro da; Dias, Gabriel Dágola; Camoleze Augusto, Andrezza Cristina de Jesus; Sartorão Filho, Carlos Izaias; Caldeirão, Talita Domingues (Seven Editora, 2023)
Climacteric is the physiological period characterized by endocrine, somatic, and psychic changes related to the termination of ovarian function in women. This process causes women to experience some of the symptom’s characteristic of climacteric syndrome, such as hot flashes or hot flashes, which are the most common. Insomnia, nervousness, depression, high blood pressure, urinary incontinence, dyspareunia, and vaginal dryness are also reported. In this context, we have prepared a review of the literature on non-hormonal treatment methods used in the relief of climacteric symptoms. In addition, we evaluate the specific benefits of each treatment. We selected 4,701 articles through a narrative literature review, which were published in the last 5 years. With this, we filtered the work done on humans, women, middle-aged women, resulting in 276 studies. From the reading of the texts, we selected 16 studies that dealt with studies on alternative therapy to hormone replacement for menopausal women. In these articles, the authors cite several drug and non-drug forms for the treatment of climacteric, but many are still inconclusive or still in the experimental phase. A new therapy under study is achieving good results and shows long-term promise for the treatment of hot flashes. DOI:https://doi.org/10.56238/innovhealthknow-021